Promoting active learning with ChatGPT: A constructivist approach in Sri Lankan higher education (Journal of Applied Learning and Teaching, 2024)
This study investigates strategies for transforming traditional didactic learning environments into active ones using ChatGPT in a resource-constrained higher education setting in Sri Lanka. It identifies 16 strategies categorized under five constructivist learning themes: active learning, social interaction, contextual learning, scaffolding, and reflective thinking. These practices leverage ChatGPT to personalize learning, foster critical thinking, encourage collaboration, enhance teaching strategies, and offer immediate feedback, addressing educational challenges in developing countries. The findings extend constructivist learning theory by demonstrating AI’s role in facilitating interactive, learner-centered experiences. The study also highlights educators’ evolving role as collaborators with AI, providing personalized support and interactive learning experiences. Practical implications include the immediate applicability of these practices in resource-constrained settings without additional resources, offering a cost-effective solution for enhancing educational quality. However, limitations such as the study’s generalizability to other contexts and the need to investigate potential negative impacts of AI are acknowledged. Future research should explore the integration of multiple AI tools and conduct similar studies in large classrooms and different contexts to enhance generalizability. Expanding this research can help leverage technology to improve educational outcomes and create sustainable, resource-efficient learning environments in the developing world.